Schottky Contact in Monolayer WS2 Field‐Effect Transistors. Issue 5 (20th February 2019) - Tang, Hao; Shi, Bowen; Pan, Yuanyuan; Li, Jingzhen; Zhang, Xiuying; Yan, Jiahuan; Liu, Shiqi; Yang, Jie; Xu, Lianqiang; Yang, Jinbo; Wu, Mingbo; Lu, Jing
Abstract: Monolayer (ML) WS2 is a promising material to be the channel of nanoscale field‐effect transistors (FETs). In ML WS2 FETs, the interfacial properties between ML WS2 and electrodes significantly affect the device performance, due to the possible existence of Schottky barriers at the interface. In this paper, the electronic and transport properties of both the lateral and the vertical interfaces between ML WS2 and six common metals is calculated (Sc, Ti, Ag, Cu, Au, and Pt) by the density functional theory and the quantum transport simulation. n ‐type Schottky contact exists with the lateral electron Schottky barrier height (SBH) of 0.28, 0.36, 0.25, 0.46, 1.00 eV for Sc, Ti, Ag, Cu, and Au electrode, respectively, while p ‐type Schottky contact exists with the lateral hole SBH of 0.98 eV for Pt electrode. The average pinning factor at the lateral interface obtained from linear fitting to the SBHs and the Schottky–Bardin model is 0.32 and 0.28, respectively, suggestive of a strong Fermi level pinning originating from the metal induced gap states. The work reveals the properties of the lateral interfaces between ML WS2 channels and electrodes theoretically for the first time, providing an instruction to design ML WS2 devices. Abstract : Monolayer WS2 is a promising material as the channel of sub 10 nm field‐effect transistors (FET). In this work, we systematically investigate the electronic and transport properties of Monolayer WS2 ‐metal contacts. The Schottky barrier heights at two kinds of interfaces in FET configurations are calculated, and the Fermi level pinning effect is analyzed.